Complicated Sporadic Cardiac Myxomas: A Second Recurrence and Myxomatous Cerebral Aneurysms in One Patient - Mazen E. Iskandar; Kamellia Dimitrova; Charles M. Geller; Darryl M. Hoffman; Robert F. Tranbaugh (Case Reports in Surgery)
A second recurrence of an excised nonfamilial cardiac myxoma is rare. Myxomatous cerebral aneurysms as a complication of cardiac myxomas are equally rare. A unique case of a patient with a total of 4 myxomas over a 20-year interval is presented. Her most recent presentation was a second recurrence of a left atrial myxoma, a de novo right atrial myxoma, and multiple cerebral myxomatous aneurysms. The challenging reconstruction of the normal anatomy was achieved with the use of porcine extracellular matrix patches. A diagnostic cerebral angiogram was later performed, and the aneurysms will be monitored for growth and possible intervention.